Effect of dietary Agriophyllum squarrosum on average daily gain, meat quality and muscle fatty acids in growing Tan lambs. (July 2023) - Liang, Yanping; Jiao, Dan; Du, Xia; Zhou, Jianwei; Degen, Abraham Allan; Ran, Fu; Sun, Guancong; Ji, Kaixi; Wu, Xiukun; Cheng, Xindong; Ma, Xiaofei; Qian, Chaoju; et al.
Abstract: The herb A. squarrosum is reputed to possess medicinal properties for humans, and has the potential to be a feed resource for livestock. We hypothesized that this herb would improve the meat quality of lambs. To test this hypothesis, 24 Tan ewe-lambs (27.7 ± 0.45 kg) were offered diets containing 0 (CON), 100 (AS100 ), 200 (AS200 ) and 300 (AS300 ) g A. squarrosum /kg DM, and average daily gain, carcass traits, blood metabolites, meat quality and fatty acid profiles were determined. Drip loss % and cooking loss % decreased with the AS100 and AS200 diets ( P  < 0.05). Dietary A. squarrosum reduced muscle fiber area and diameter and increased density of the meat ( P  < 0.05), which indicated that the meat was more tender. The concentrations of C10:0 and C18:1n-9 t were 1ower and of C17:0 and C18:3n-3 were greater in the AS200 and AS300 treatments than CON ( P  < 0.05). Our results suggest that feeding lambs up to 200 g/kg DM of A. squarrosum can increase the water-holding capacity and L* value of meat without compromising growth. Further research is needed to determine the optimal level. Highlights: Agriophyllum squarrosum increased the water-holding capacity and L* value of meat. squarrosum improved muscle fiber characteristics making the meat more tender. Feed-to-gain ratio was greater in lambs fed the AS300 diet than control lambs. A daily intake of 100–200 g A. squarrosum /kg DMI can benefit growing lambs.